Análise da variabilidade climática na região de integração lago de Tucuruí, Estado do Pará - NEVES JÚNIOR, Walter Luis Teixeira (2018)
The present work aims to make a spatial and temporal analysis of climatic variability in the Tucuruí Lake Region of Integration (RI), in the State of Pará, earsten portion of the Brazilian Amazonia, correlating the rainfall indices with the atmospheric systems that characterize the climate of the region. They were associated with the reservoir formation of the Tucuruí Hydrelectric Power Plant. Rainfall data were obtained from seven meteorological stations, and downloaded from the HidroWeb / ANA system and from the Meteorological Database for Teaching and Research / INMET, from which the complete climatological normal of the Tucuruí Station was also obtained. After the data were systematized in the Hidro 1.3.0 software, they were organized in Microsoft Excel spreadsheets, to analyze the pluviometric regime and the seasonality for the entire IR in the period 2000-2016 and, specifically, to the Tucuruí Station from 1972, by parameter the complete and provisional climatological normals established by the World Meteorological Organization (WMO). The results obtained were totally within the expected for the performance of the main rainfall systems in the Amazon, with a clear south-north variation of the pluviometric regime. With regard to seasonality, the concentration of rains was confirmed in summer and autumn, while in winter there is a drier period. The classification of the degree of intensity of the rains indicated the influence of El Niño (ENSO) and La Niña anomalies on extreme (sub) drought and rainfall events in the Tucuruí Lake RI. The comparisons between complete and provisional climatological normals of Tucuruí showed a slight increase in the rainfall indices during the analyzed period (1972-2016), which provides elements to suppose a local change in pluviometric regime between the pre- and post-filling phases of the reservoir of the HPP of Tucuruí. For the Tucuruí Lake Region as a whole, slight changes were also observed, mainly the reduction of total rainfall at the end of the rainy season and in the less rainy period.